SISTEM REKOMENDASI PENENTUAN JUDUL SKRIPSI MENGGUNAKAN ALGORITMA DECISION TREE - A Sofalul Khazari; Fitri Marisa; Indra Dharma Wijaya (Universitas Merdeka Malang, 2017)
One of the requirements to obtain a Bachelor's degree, a student must make a thesis. Thesis is a scientific work that is used as a good condition in Private Universities (PTS) and State Universities (PTN) in Indonesia. In the thesis, students are required to apply science according to the field of science that has been pursued. However, the reality of existing students are still confused in determining the title or field that will be discussed in the thesis. Therefore, the authors try to make a recommendation system of thesis title determination that can help students Informatics Engineering University of Widyagama Malang to determine the title of the thesis in accordance with the capabilities and standards determined by the department. With the method of Decision tree using ID3 algorithm, it is expected this system can help students to not difficulty in determining the title of the thesis. DOI: https://doi.org/10.26905/jtmi.v3i1.1248